The Influence of Health Consciousness, Environmental Consciousness, Social Influence, Brand Awareness and Brand Trust on Consumer Purchase Intention in Organic Skin Care Industry - Jinying, Liu (2019)
Dissertação de Mestrado em Marketing apresentada à Faculdade de Economia